Harmonic current and voltage compensation using HSAPF based on hybrid control approach for synchronous reference frame method. (February 2016) - Swain, Sushree Diptimayee; Ray, Pravat Kumar
Abstract: This paper presents a Hybrid Series Active Power Filter (HSAPF) for compensation of source current and load voltage harmonics. The HSAPF combination consists of a small rated series active power filter and a shunt connected passive power filter. This combination is suitable for compensation of voltage-type as well as current-type harmonic producing load. The HSAPF uses the synchronous rotating reference frame method that based on hybrid control approach, which eliminate both source current as well as load voltage harmonics and also tests the performance of HSAPF for ideal voltage, non-ideal voltage and also at different loading conditions, etc.